Challenges of inverter-based load disaggregation - Cruz, Marcos Vicente [UNESP]; Bernardino, Luiz Gustavo Reis [UNESP]; Marafao, Fernando Pinhabel [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This document addresses the challenges of disaggregating techniques for non-intrusive load monitoring (NILM) of inverter-based loads. Although inverter-based loads are more energy efficient they add an extra layer of complexity for NILM-based algorithms because of their variable energy consumption and rapid variations. There are few studies regarding these types of loads and they do not cover every combination of loads such as several inverter-based loads in the same energy network. There are several questions on whether or not such algorithms can be used for real-time applications because of their apparent high computational need and their storage requirements to perform the disaggregation.
Keywords: artificial intelligence; energy management; inverter-based load; load identification; NILM; Disaggregation; Energy; Energy efficient; Energy networks; Energy-consumption; Inverter-based; Inverter-based load; Load identification; Nonintrusive load monitoring; Rapid variation